NUMERICAL SIMULATION FOR RADICAL SUPPORT STRUCTURE OF LNG FUEL TANK UNDER IMPACT LOAD - MA HanYang; DONG JinShan; FAN Sen; ZHAI XiaoChen; WANG JianJun (Jixie qiangdu)
The radial structural support made of epoxy FRP（ fiber reinforced plastic） of LNG fuel tank bears considerable compressive stress under impact load. However,it is hard to bear out of plane tensile stress and interlaminar shear stress. Thus,reasonable installation angle of pipes effectively guarantees the support ability of the epoxy FRP pipes. Based on it,the commercial finite element codes ANSYS with the method of fluid-structure coupling was used to stimulate the force condition of the epoxy FRP pipes,the correlation between the force of epoxy FRP pipes and installation angle of pipes was obtained. According to strength check of shear stress,radical tensile stress and the failure theory of Hoffman,the optimal installation angle of upper pipes was 30° and 60° of below the pipes. This study had an important reference value for safe operation of LNG fuel tank.